EFEITO DO SELAMENTO DENTINÁRIO IMEDIATO NA RESISTÊNCIA À FRATURA E MODO DE FALHA DE ENDOCROWNS ANTERIORES (CIPEEX, 2025)
The restoration of severely compromised endodontically treated teeth remains a challenge in contemporary dentistry. The risk of catastrophic root fractures can be reduced by using approaches without intraradicular posts, such as endocrowns, which have recently been studied even for anterior teeth. Because these are innovative approaches, the first studies on anterior endocrowns are laboratory-based, which may influence the measured fracture resistance. Optimized adhesion to dentin through immediate dentin sealing (IDS) is particularly important for endocrowns, as micromechanical retention plays a key role in restoration stability. This study aimed to evaluate the influence of the timing of dentin hybridization on the fracture resistance and failure mode of anterior endocrowns in severely compromised roots. Twenty bovine roots were divided into two groups (n = 10): immediate dentin sealing (IDS) and delayed dentin sealing (DDS). In the IDS group, dentin was hybridized immediately after tooth preparation, whereas in the DDS group dentin was hybridized only at the time of final cementation. All roots were restored with CAD/CAM nanoceramic resin endocrowns. Groups underwent fracture resistance testing at 1 mm/min, with a load applied at 30 degrees using a flat resin surface with three quarters contact on the incisal edge of the endocrown. Failure mode was classified as repairable (fracture limited to the restoration), possibly restorable (root fracture above the acrylic base insertion), or catastrophic (root fracture extending below the acrylic base insertion). Means of fracture resistance under static loading were compared with Student’s t-test. The IDS group showed higher fracture resistance (IDS: 400 N ± 55.6; DDS: 291 N ± 48.7), whereas the DDS group had fewer catastrophic fractures. We conclude that the timing of dentin hybridization influences the fracture resistance of anterior endocrowns.
Keywords: Dental crown; Non-vital tooth; Dentin bonding; Fracture resistance